Missile Injury of the Sciatic Nerve: Observational Study Supporting Early Exploration and Direct Suture With Flexed Knee. Issue 11 (20th April 2019) - Mathieu, Laurent; Pfister, Georges; Murison, James Charles; Oberlin, Christophe; Belkheyar, Zoubir
Abstract: Missile injuries of the sciatic nerve are frequently encountered in modern violent conflicts. Gunshot and fragment wounds may cause large nerve defects, for which management is challenging. The great size of the sciatic nerve, in both diameter and length, explains the poor results of nerve repair using autografts or allografts. To address this issue, we used a simple technique consisting of a direct suture of the sciatic nerve combined with knee flexion for 6 weeks. Despite a published series showing that this procedure gives better results than sciatic nerve grafting, it remains unknown or underutilized. The purpose of this cases study is to highlight the efficiency of direct sciatic nerve coaptation with knee flexed through three cases with missile injuries at various levels. At the follow-up of two years, all patients were pain free with a protective sensory in the sole and M3+ or M4 gastrocnemius muscles, regardless of the injury level. Recovery was also satisfying in the fibular portion, except for the very proximal lesion. No significant knee stiffness was noticed, including in a case suffering from an associated distal femur fracture. Key points to enhance functional recovery are early nerve repair (as soon as definitive bone fixation and stable soft-tissue coverage are achieved) and careful patient selection.